Potential Exposure to Arsenic from Infant Rice Cereal - Courtney C. Carignan; Tracy Punshon; Margaret R. Karagas; Kathryn L. Cottingham (Ubiquity Press, 2016)
Background: Rice is known to be high in arsenic, including in infant rice cereal. Although arsenic in drinking water is currently regulated, there are currently no US regulations regarding arsenic concentrations in food. Objective: We used published values to estimate arsenic exposure via rice cereal relative to breast milkor formula for 6- to 12-month-old infants in the general US population. Results: We found that arsenic exposure from 3 servings of rice cereal exceeded that of formula made with water containing arsenic at 10 μg/L, the US Environmental Protection Agency maximum contaminant level. Conclusions: Our findings suggest that rice cereal can markedly increase arsenic exposure among US infants relative to breast milk and formula.